A rightward shift of the distribution of fasting and post‐load glucose in northern Sweden between 1990 and 2009 and its predictors. Data from the Northern Sweden MONICA study. Issue 9 (23rd May 2013) - Lilja, M.; Eliasson, M.; Eriksson, M.; Söderberg, S.
Abstract Aims Most Swedish studies show stable diabetes prevalence despite increasing obesity, but glucose levels may shift upwards below the diagnostic threshold for diabetes. Our aim was to explore trends in glucose distribution in northern Sweden; whether these trends were uniformly distributed throughout the spectrum of glucose concentrations; and to relate trends to traditional risk factors and the obesity‐related adipokine leptin. Methods The project consisted of four cross‐sectional surveys between 1990 and 2009, with 7069 participants aged 25–64 years. The overall participation rate was 74.4%. Trend analyses of glucose concentrations along the entire distribution and linear regression in relation to survey years and risk markers were used. Results Fasting and post‐load glucose increased in women (both P < 0.001) and post‐load glucose in men (P = 0.004). The increase was seen in most deciles of glucose concentrations. The prevalence of impaired glucose tolerance doubled in women to 14.5% and tripled in men to 10.1% (both P = 0.004). The prevalence of impaired fasting glucose rose in women from 4.5 to 7.7% (P < 0.001). The prevalence of diabetes was unchanged—6.4% in 2009. In men, leptin, together with traditional risk factors, explained 7.8 and 10.8% of the variance in fasting (P = 0.008) and post‐load (P < 0.001) glucose, respectively. Conclusions Increasing fasting and post‐load glucose concentrations were seen in most deciles of the glucose distribution, indicating a shift in the entire population. Leptin was significantly associated with fasting and post‐load glucose in men.